Formation of substrate-based gold nanocage chains through dealloying with nitric acid - Yan, Ziren; Wu, Ying; Di, Junwei (Beilstein Journal of Nanotechnology, 2015)
Metal nanocages have raised great interest because of their new properties and wide applications. Here, we report on the use of galvanic replacement reactions to synthesize substrate-supported Ag–Au nanocages from silver templates electrodeposited on transparent indium tin oxide (ITO) film coated glass. The residual Ag in the composition was dealloyed with 10% nitric acid. It was found that chains of Au nanocages were formed on the substrate surface during dealloying. When the concentration of HNO3 increased to 20%, the structures of nanocages were damaged and formed crescent or semi-circular shapes. The transfer process on the substrate surface was discussed.
Keywords: dealloying; gold nanocage chains; nitric acid; solid substrate

(untitled) - Skrabalak, S. E.; Chen, J.; Au, L.; Lu, X.; Li, X.; Xia, Y. (Adv. Mater., 2007)

(untitled) - Skrabalak, S. E.; Chen, J.; Sun, Y.; Lu, X.; Au, L.; Cobley, C. M.; Xia, Y. (Acc. Chem. Res., 2008)

(untitled) - Chen, J.; Yang, M.; Zhang, Q.; Cho, E. C.; Cobley, C. M.; Kim, C.; Glaus, C.; Wang, L. V.; Welch, M. J.; Xia, Y. (Adv. Funct. Mater., 2010)

(untitled) - Zhang, Q.; Cobley, C. M.; Zeng, J.; Wen, L.-P.; Chen, J.; Xia, Y. (J. Phys. Chem. C, 2010)

(untitled) - Huang, D.; Hu, T.; Chen, N.; Zhang, W.; Di, J. (Anal. Chim. Acta, 2014)

(untitled) - Zhang, Y.; Sun, Y.; Liu, Z.; Xu, F.; Cui, K.; Shi, Y.; Wen, Z.; Li, Z. (J. Electroanal. Chem., 2011)

(untitled) - Panfilova, E.; Shirokov, A.; Khlebtsov, B.; Matora, L.; Khlebtsov, N. (Nano Res., 2012)

(untitled) - Li, W.; Cai, X.; Kim, C.; Sun, G.; Zhang, Y.; Deng, R.; Yang, M.; Chen, J.; Achilefu, S.; Wang, L. V.; Xia, Y. (Nanoscale, 2011)

(untitled) - Demeritte, T.; Fan, Z.; Sinha, S. S.; Duan, J.; Pachter, R.; Ray, P. C. (Chem. – Eur. J., 2014)

(untitled) - Zeng, J.; Zhang, Q.; Chen, J.; Xia, Y. (Nano Lett., 2010)

(untitled) - Yen, C. W.; Mahmoud, M. A.; El-Sayed, M. A. (J. Phys. Chem. A, 2009)

(untitled) - Hu, J.; Chen, M.; Fang, X.; Wu, L. (Chem. Soc. Rev., 2011)

(untitled) - Zhang, Q.; Wang, W.; Goebl, J.; Yin, Y. (Nano Today, 2009)

(untitled) - Cobley, C. M.; Xia, Y. (Mater. Sci. Eng., R, 2010)

(untitled) - Sun, Y.; Xia, Y. (Science, 2002)

(untitled) - Gilroy, K. D.; Farzinpour, P.; Sundar, A.; Tan, T.; Hughes, R. A.; Neretina, S. (Nano Res., 2013)

(untitled) - Gilroy, K. D.; Sundar, A.; Farzinpour, P.; Hughes, R. A.; Neretina, S. (Nano Res., 2014)

(untitled) - Chen-Wiegart, Y. K.; Wang, S.; McNulty, I.; Dunand, D. C. (Acta Mater., 2013)

(untitled) - Gwak, E.-J.; Kang, N.-R.; Baek, U. B.; Lee, H. M.; Nahm, S. H.; Kim, J.-Y. (Scr. Mater., 2013)

(untitled) - Chen, A. Y.; Shi, S. S.; Qiu, Y. D.; Xie, X. F.; Ruan, H. H.; Gu, J. F.; Pan, D. (Microporous Mesoporous Mater., 2015)

(untitled) - Maier, I. A.; Fernández, S. A.; Galvele, J. R. (Corros. Sci., 1995)

(untitled) - Lu, X.; Au, L.; McLellan, J.; Li, Z.-Y.; Marquez, M.; Xia, Y. (Nano Lett., 2007)

(untitled) - Yan, Z.; Peng, Y.; Wu, Y.; Di, J. (ChemElectroChem, 2015)

(untitled) - Peng, Y.; Yan, Z.; Wu, Y.; Di, J. (RSC Adv., 2015)

(untitled) - Hu, T.; Lin, Y.; Yan, J.; Di, J. (Spectrochim. Acta, Part A, 2013)

(untitled) - Dong, P.; Lin, Y.; Deng, J.; Di, J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Sun, Y.; Xia, Y. (J. Am. Chem. Soc., 2004)

(untitled) - Sun, Y.; Xia, Y. (Anal. Chem., 2002)

(untitled) - Mahmoud, M. A.; El-Sayed, M. A. (Langmuir, 2012)

(untitled) - Wu, H.; Wang, P.; He, H.; Jin, Y. (Nano Res., 2012)

(untitled) - Martínez, L. L.; Segarra, M.; Fernández, M.; Espiell, F. (Metall. Trans. B, 1993)